Konstruksi Passion Dalam Film Animasi "Soul" - Susanto, Syafiyah Nabilla; Wibowo, Tangguh Okta (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Passion is a strong tendency towards an activity that is highly liked, loved, and appreciated by individuals that makes them willing to give all of their time and energy to do these activities. This study aims to determine the construction of passion which is contained in Disney and Pixar’s animated film Soul”. To understand that, this study will be examined using Roland Barthes’s semiotics analysis which contains the orders of significations consisting of denotation, connotation, and myth. This research will also be examined using the theory of social construction of reality proposed by Peter L. Berger and Thomas Luckmann. This study found that passion can be found and developed by every individuals. Moreover, passion is not only attached to one's body but also to one's soul, so that makes passion really difficult to completely eliminate from one’s self.